2020
DOI: 10.1101/2020.06.01.127571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of antibiotic action shape the fitness landscapes of resistance mutations

Abstract: 1 Antibiotic-resistant pathogens are a major public health threat. Understanding how an 2 antibiotic's mechanism of action influences the emergence of resistance could help to 3 improve the design of new drugs and to preserve the effectiveness of existing ones. To this 4 end, we developed a model that links bacterial population dynamics with antibiotic-target 5 binding kinetics. Our approach allows us to derive mechanistic insights on drug activity from 6 population-scale experimental data and to quantify the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…It is widely accepted that plasmid-mediated horizontal gene transfer (HGT) of drug-resistance genes plays a crucial role in promoting the evolution of bacterial drug resistance [51]. Bacteria can acquire antibiotic resistance from plasmids, survive and become dominant strains in a natural selection where antibiotics are present [52,53]. Even though plasmid-carrying usually imposes an adaptation cost on the host bacterium, causing the limitation of its spread, the cost can be mitigated over time by compensating mutations [51,54].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that plasmid-mediated horizontal gene transfer (HGT) of drug-resistance genes plays a crucial role in promoting the evolution of bacterial drug resistance [51]. Bacteria can acquire antibiotic resistance from plasmids, survive and become dominant strains in a natural selection where antibiotics are present [52,53]. Even though plasmid-carrying usually imposes an adaptation cost on the host bacterium, causing the limitation of its spread, the cost can be mitigated over time by compensating mutations [51,54].…”
Section: Discussionmentioning
confidence: 99%
“…under the effect of treatment), then sometimes referring to them as fitness seascapes, has important consequences for the understanding of adaptation, such as resistance evolution (Lässig et al, 2017; King et al, 2022). For example, Hemez et al (2020) found in a simulation study that the drug mode of action (bacteriostatic vs. bactericidal) was changing the shape of the fitness landscape. In line with this, we have found that both density-affecting and trait-affecting treatment types alter trait adaptation trajectories.…”
Section: Discussionmentioning
confidence: 99%